On the Robustness of Size and Book-to-Market in Cross-Sectional Regressions - Knez, Peter J.; Ready, Mark J. (Journal of Finance, 1997)
We use a robust regression estimator to analyze the risk premia on size and book-to-market. We find that the risk premium on size that was estimated by Fama and French (1992) completely disappears when the 1% most extreme observations are trimmed each month. We also show that the negative average of the monthly size coefficients reported by Fama and French can be entirely explained by the 16 months with the most extreme coefficients. We argue that further investigation of these results could lead to an understanding of the economic forces underlying the size effect, and may also yield important insights into how firms grow.